2007
DOI: 10.2478/s11535-007-0009-y
|View full text |Cite
|
Sign up to set email alerts
|

The effect of aluminium on bioelectrical activity of the Nitellopsis obtusa cell membrane after H+-ATPase inhibition

Abstract: Aluminium induced membrane potential (E m ) changes and potential changes during repolarization phase of the action potential (AP) in the internodal cells of Nitellopsis obtusa after blocking H + -ATPase activity by DCCD were investigated. Micromolar concentrations of DCCD are sufficient togive complete and irreversible inhibition of proton pumping. The membrane potential was measured by conventional glass-microelectrode technique. We found that the half-amplitude pulse duration differs significantly between s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 27 publications
(33 reference statements)
1
3
0
Order By: Relevance
“…We propose to measure the width of AP at 50 mV repolarisation from the AP peak (Kisnieriene et al 2016) for evaluation of the effect of nickel (a moderately toxic metal) on K + channels. In another investigation we found that the average duration of half amplitude was 4.9 AE 0.65 s in control conditions, 7.7 AE 0.72 s in DCCD and 17 AE 2.36 s after addition of aluminium (Kisnierienë and Sakalauskas 2007). Our results clearly show that Al modulates the repolarisation process by increasing its duration (Sevriukova et al 2014b).…”
Section: Action Potential Pattern As a Biomarker Of Bc Effects On Memsupporting
confidence: 64%
“…We propose to measure the width of AP at 50 mV repolarisation from the AP peak (Kisnieriene et al 2016) for evaluation of the effect of nickel (a moderately toxic metal) on K + channels. In another investigation we found that the average duration of half amplitude was 4.9 AE 0.65 s in control conditions, 7.7 AE 0.72 s in DCCD and 17 AE 2.36 s after addition of aluminium (Kisnierienë and Sakalauskas 2007). Our results clearly show that Al modulates the repolarisation process by increasing its duration (Sevriukova et al 2014b).…”
Section: Action Potential Pattern As a Biomarker Of Bc Effects On Memsupporting
confidence: 64%
“…The PM H + -ATPase activity can be inhibited by the specific inhibitor DCCD (Kisnierienë and Sakalauskas 2007). In this research, DCCD was used to identify the function of PM H + -ATPase in regulating rhizosphere pH.…”
Section: Resultsmentioning
confidence: 99%
“…A microelectrode was inserted into the cell and electrical properties of the PM were measured post 1 h of insertion. Action potentials were elicited 6 times every five minutes in each solution ( Figure 1) by injecting depolarizing current (0.1 s duration 1 μA/ cm 2 square pulse) between two pools using Ag/AgCl wires [17].…”
Section: Methodsmentioning
confidence: 99%